2021
DOI: 10.1177/03635465211007139
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold With Natural Calcified Cartilage Zone for Osteochondral Defect Repair in Minipigs

Abstract: Background: Long-term outcomes of current clinical interventions for osteochondral defect are less than satisfactory. One possible reason is an ignorance of the interface structure between cartilage and subchondral bone, the calcified cartilage zone (CCZ). However, the importance of natural CCZ in osteochondral defects has not been directly described. Purpose: To explore the feasibility of fabricating trilayer scaffold containing natural CCZ for osteochondral defects and the role of CCZ in the repair process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…[54][55][56] It has been known that the CCL is a transition zone connecting the cartilage and bone parts, mainly containing hypertrophic chondrocytes that transform from chondrocytes and then are calcified to form osteoblasts. 57,58 It is suggested that the D-ECMs derived from osteoblasts, Cho, and HCho should all have a large or small effect on BMSC hypertrophy. Herein, we explored this issue using the D-ECMs derived from these cell origins by culturing a cell sheet on PLLA/Gel fibrous mesh and subsequent decellularization, followed by re-seeding BMSCs onto the D-ECMs to evaluate the extent of BMSC hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] It has been known that the CCL is a transition zone connecting the cartilage and bone parts, mainly containing hypertrophic chondrocytes that transform from chondrocytes and then are calcified to form osteoblasts. 57,58 It is suggested that the D-ECMs derived from osteoblasts, Cho, and HCho should all have a large or small effect on BMSC hypertrophy. Herein, we explored this issue using the D-ECMs derived from these cell origins by culturing a cell sheet on PLLA/Gel fibrous mesh and subsequent decellularization, followed by re-seeding BMSCs onto the D-ECMs to evaluate the extent of BMSC hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were allowed to warm to room temperature, then stained with hematoxylin-eosin (HE) and Sirius Red as previously described ( Liu et al, 2017 ; Huang et al, 2021 ). Sections were examined using a BX40 light microscope (Olympus, Feasterville, PA, United States) and photographed at magnifications of ×0.5–20.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, scaffold-based strategies have been made with their structure, composition, and mechanical and biological properties exquisitely tailored through various chemical modifications such as by incorporating inorganic bioceramics or bioglasses [ 102 , 103 ]. More importantly, a CCL barrier allowing the transportations of oxygen and nutrition while minimizing cell passage can be obtained by both densifying the layer and reducing the pore size [ 98 ].Recent studies on trilayered scaffolds with an intermediate dense layer exhibited not only superior regeneration of hyaline-like cartilage and subchondral bone tissue in vivo [ [104] , [105] , [106] ], but also improved mechanical properties of the neo-formed tissues compared to bilayered scaffolds [ 64 , 104 ].…”
Section: Biomimetic Architectures In Mzsmentioning
confidence: 99%
“…Besides these examples of multilayer lyophilization process, lyophilization is often used in combination with other techniques to fabricate MZSs. Huang et al [ 105 ] recently used lyophilization to bond type II collagen sponge and acellular normal pig subchondral bone, where a natural CCZ was included by removing the hyaline cartilage above the CCZ of pig knee. Such prepared scaffold showed a well-integrated morphology with a trilayered structure and exhibited excellent in vivo OC repair in a minipig knee joint defect model.…”
Section: Novel Fabrications Techniquesmentioning
confidence: 99%